José Saramago, leitor dos historiadores: tensões entre a literatura, a epistemologia histórica e o pós-modernismo em História do cerco de Lisboa - Roque da Silva, Mateus (2022)
The present dissertation is dedicated to the investigation, understanding and analysis of the dialogues, in their theoretical-methodological aspect, that José Saramago, a declared Marxist, established with the historians of his time, delimited here between the years of 1970 and 1980, when producing the novel The History of the Siege of Lisbon, originally published in 1989. This period, in the dissonant perception of some theorists (HUTCHEON, 1991; EAGLETON, 1998; HARVEY, 2016), can be categorized as postmodern, a period in which the fragmentation of subjects and discredit in modern metanarratives – religious, political, historical, aesthetic, etc. (LYOTARD, 2020). In the same direction, certain critics of José Saramago (ARNAUT, 2002; REIS, 2004; REDU, 2015) lead him to dialogue with these philosophicalpoetic assumptions, while for others (PETROV, 2014; PAPKE, 2021; SILVA, 2022), his stance is markedly Marxist, centered on historical-dialectical materialism and on the perspective of total History. Faced with this dispute, the present study will present and analyze the postmodern paradigm, contrasting it, in the first chapter, with the postulates favorable and unfavorable to the affiliation of the Portuguese author to theparadigm in question. From the considerations of Petar Petrov (2014) and Vera Silva (2022), we will direct our argument, in the second chapter, to the reading of José Saramago as a reader Karl Marx (2011) and the Annales, especially in relation to the productions of Georges Duby (1988). In this way, we will focus our analysis on the conception of total History, central to the thought of the German philosopher and his French readers, verifying how it is aesthetically materialized in Saramago's poetic production of a historical nature, especially in The History of the Siege of Lisbon. That said, in the third chapter, we will effectively enter the novel, showing how the protagonist Raimundo Silva, a reviewer who becomes, throughout the narrative, the author of a second "History of the siege of Lisbon", shows himself, somewhat mirroring its creator, producer of a narrative that, from a perception that approaches the Evidential Paradigm of Carlo Ginzburg (1989), pays attention to the gaps and missing details of the official historical discourse, seeking to achieve, thus, a historical totality, as Marx (2011) wants, previously excluded from the aforementioned historiographical aspect.